Pathways from relative deprivation to individual violence: the effect of subjective perception and emotional resentment in South Korea - Park, Seong min (The British journal of criminology, 2021)
Criminological studies assert that individuals’ psychological cognition and emotional resentment mediate the effect of economic deprivation on individual violence; however, a limited number of studies have empirically addressed these subjective mediations. Furthermore, the effect of relative deprivation in Asian counties is seldom investigated. To fill this gap, we construct theoretical path models and examine the argument of relative deprivation in South Korea. A total of 2,040 individuals are surveyed face to face through stratified random sampling. The results show that the objective status of economic inequality does not directly affect individual violence. We conclude that the subjective perception of deprivation and emotional response are essential mediators for the effect of economic deprivation on individual violence.